The Feminization of Female Figures in Spanish Women's Poetry of the 1980s - Sharon Keefe Ugalde (Studies in 20th & 21st Century Literature, 1992)
The paper examines how women poets appropriate and transform man-made biblical and literary figures—Eve, Lot's wife, and Ophelia—in order to express female meaning. Poetry by women published since the democratization of Spain in the late 1970s serves as the basis of the study. Three strategies of feminization stand out. Enhancement reflects the predicament of poets living roles imposed by male denomination, but sensing the presence of a silenced, imprisoned self. Subversion is aimed at dismantling patriarchally defined reality, and revision corresponds to the constructive task of self-discovery. Poets, for example, embrace Ophelia, recognizing that their desperation (like hers) is rooted in patriarchal order, and subvert the image of Lot's wife into a demand for autonomy. Eve is revised to communicate the awareness that female subjectivity is closely bound to female eroticism, and perhaps most astonishingly, poor, helpless Ophelia comes to symbolize woman's new freedom and power to inscribe herself.
Keywords: women poets; Spanish women poets; biblical figures; literary figures; Eve; Lot& #x27; s wife; Ophelia; female; male; female meaning; male domination; subversion; patriarchy; self-discovery; autonomy; power; eroticism